2015
DOI: 10.4155/fmc.15.63
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Binding Thermodynamics on Medicinal Chemistry Optimizations

Abstract: Background: Ligand binding thermodynamics has been attracted considerable interest in the past decade owing to the recognized relation between binding thermodynamic profile and the physicochemical and druglike properties of compounds. Discussion: • Affinity improvements in drug discovery optimizations can be either enthalpically or entropically driven. In this review the relation between optimization strategies and ligand properties are presented based on the structural and thermodynamic analysis of ligand-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The strategy is to discriminate, as far as possible, between the enthalpic efficiency and entropy profile (ΔH driven > ΔS driven) but to have both and consequently to have a good balanced affinity between these two thermodynamic functions. 32,33 In addition, we chose this site for substitution due to the easy chemical transformations. Thus, as shown in Scheme 1, the synthesis of ring A analogues began with a simple Suzuki cross-coupling reaction between 5-bromo-7-azaindole 5 and heteroaryl/aryl boronic acids (6a−s), 34,35 which gave 5-aryl/hetroaryl substituted 7-azaindoles (7a−s) in good yields (60−95%).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The strategy is to discriminate, as far as possible, between the enthalpic efficiency and entropy profile (ΔH driven > ΔS driven) but to have both and consequently to have a good balanced affinity between these two thermodynamic functions. 32,33 In addition, we chose this site for substitution due to the easy chemical transformations. Thus, as shown in Scheme 1, the synthesis of ring A analogues began with a simple Suzuki cross-coupling reaction between 5-bromo-7-azaindole 5 and heteroaryl/aryl boronic acids (6a−s), 34,35 which gave 5-aryl/hetroaryl substituted 7-azaindoles (7a−s) in good yields (60−95%).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Compounds tend to be larger and increasingly hydrophobic with improving affinity. This is, however, not beneficial, since large and hydrophobic compounds have unfavorable physicochemical properties and are more prone to suboptimal ADME profile as it was shown by the comparison of compounds from various stages of the discovery process [45,[48][49][50][51]. It was also shown that property inflation is a general phenomenon and is basically independent from the hit identification strategy, rather it could be traced back to optimization practices [7].…”
Section: Thermodynamics and Drug-like Propertiesmentioning
confidence: 99%